Climate Change and Community Resilience: Insights from South Asia - Shrestha, Kiran (Economic Journal of Development Issues, 2023)
This book presents case studies, stories and examples of climate change adaptation initiatives from seven South Asian countries—Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka—highlighting traditional and indigenous knowledge with community engagement. The book has 27 studies (chapters) organized under six themes (Parts): concepts and models; traditional knowledge and sustainable agriculture; technology adoption; disaster risk reduction; urban sustainability; and alternative livelihoods.